Optimization and evaluation of the ARCHITECT Chagas assay and in-house ELISA for Chagas disease in clinical settings in Japan. (February 2021) - Imai, Kazuo; Murakami, Takashi; Misawa, Kazuhisa; Fujikura, Yuji; Kawana, Akihiko; Tarumoto, Norihito; Maesaki, Shigefumi; Maeda, Takuya
Abstract: Approximately 250, 000 immigrants from Latin America live in Japan and it is estimated that 1500–3000 of them are potentially infected with Trypanosoma cruzi, the cause of Chagas disease. Therefore, the establishment of a standardized diagnostic method for Chagas disease in Japan is urgently needed. In this study, we optimized and evaluated the ARCHITECT Chagas assay and in-house ELISA for Chagas disease in clinical settings. In particular, we evaluated the performance of ARCHITECT Chagas as well as ELISA with whole-cell lysates and three recombinant proteins (TcF, TcBCDE, and CP1 + CP3) using 93 Chagas disease-positive serum samples and 108 Chagas disease-positive samples. The sensitivities of ARCHITECT Chagas, whole-cell lysate, TcF, TcBCDE, and CP1 + CP3 ELISA were respectively 100%, 100%, 98.9%, 98.9%, and 89.2% and the corresponding specificities were 100%, 99.1%, 99.1%, 100%, and 99.1%. False-positive results were obtained for whole-cell lysate, TcF, and CP1 ± CP3 ELISA. This is the first evidence that OD cut-off values optimized for in-house ELISA are similar in terms of sensitivity and specificity to those of the ARCHITECT Chagas test, supporting the use of these in-house assays as diagnostic tests for Chagas disease in the clinical setting in Japan. Graphical abstract: Unlabelled Image Highlights: Standardized diagnostic methods for Chagas disease are needed in Japan. The ARCHITECT Chagas assay had the highest sensitivity and specificity. In-house ELISA with various recombinant proteins had good diagnostic performance. In-house ELISAs are suitable for primary screening in terms of cost.